2013
DOI: 10.1080/10168737.2013.787110
|View full text |Cite
|
Sign up to set email alerts
|

Resource Curse: New Evidence on the Role of Institutions

Abstract: This paper attempts to provide a probable answer to a longstanding resource curse puzzle;i.e., why resource-rich nations grow at a slower rate compared to less fortunate ones. Using an innovative threshold estimation technique, the empirical results reveal that there is a threshold effect in the natural resources -economic growth relationship. We find that the impact of natural resources is meaningful to economic growth only after a certain threshold point of institutional quality has been attained. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 22 publications
3
50
0
5
Order By: Relevance
“…Rather than trying to explain any variability in institutions as a result of mineral abundance, it instead emphasises the mediating role of good institutions in preventing the resource curse (Boschini et al, 2007;Kolstad, 2009;Mehlum et al, 2006b;Sarmidi et al, 2014). The preventive role of good institutions against rentseeking is, for example, discussed by Tornell and Lane (1999), who show how weak institutions interacting with a mineral boom can induce a 'voracity effect' with numerous interest groups competing for the rents (see also Boschini et al, 2007 who link the appropriability of mineral rents, and hence the incentive to rent-seek, on institutional quality proxied by the extent of property rights protection).…”
Section: Institutions (As Mediating Variable)mentioning
confidence: 99%
“…Rather than trying to explain any variability in institutions as a result of mineral abundance, it instead emphasises the mediating role of good institutions in preventing the resource curse (Boschini et al, 2007;Kolstad, 2009;Mehlum et al, 2006b;Sarmidi et al, 2014). The preventive role of good institutions against rentseeking is, for example, discussed by Tornell and Lane (1999), who show how weak institutions interacting with a mineral boom can induce a 'voracity effect' with numerous interest groups competing for the rents (see also Boschini et al, 2007 who link the appropriability of mineral rents, and hence the incentive to rent-seek, on institutional quality proxied by the extent of property rights protection).…”
Section: Institutions (As Mediating Variable)mentioning
confidence: 99%
“…He suggests that heavily oil-dependent countries lack the institutional mechanism to de-link fiscal expenditures from current resource revenues which in turn leads to myopic and pro-cyclical macroeconomic policy. Sarmidi et al (2014) identified another threshold effect in terms of institutional quality. Using the dataset by Brunnschweiler and Bulte (2008) they found a non-linear relation between resource-driven growth and the quality of institutions.…”
Section: The Institutional Conditionmentioning
confidence: 99%
“…Classic theories suggest that resource abundance has positive development effects as windfalls from extraction boost real living standards by supporting higher levels of consumption, investment, and public spending. The subsequent demand expansion gives the necessary big-push to the economy and helps to escape the low-income equilibrium trap (Sachs & Warner, 1999). Spill-overs from primary extraction generate incentives for the investors to incur the relatively high costs of industrialisation while government revenues create an opportunity to finance core public goods such as education, healthcare, or physical infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Brunnschweiler and Bulte (2008) An increasing number of studies has also devoted attention to how institutions can condition the effect of mineral wealth on several development outcomes. Good institutions that ensure property rights protection can discourage rent-seeking behaviour in mineral-rich contexts and, hence, prevent resource curse phenomena and stimulate economic development (Boschini, Pettersson, & Roine, 2007;Sarmidi, Law, & Jafari, 2014). The core message of these studies is that good institutions (in the form of secure property rights, efficient bureaucracies and low corruption) improve resource windfall management and can turn the curse into a blessing (El Anshasy & Katsaiti, 2013, Mehlum, Moene, & Torvik, 2006.…”
Section: The Resource Curse: the Evolution Of The Literaturementioning
confidence: 99%